Analysis Of Payroll Accounting Information Systems In An Effort To Improve The Effectiveness Of Internal Control At Pt Perkebunan Nusantara IV Medan - Adella, Cindy (Indonesian Journal of Economics and Finance, 2025)
Payroll accounting information system is a system designed to facilitate precise and accurate employee salary calculation transactions. The purpose of this research is to find out the payroll accounting information system that has been implemented by PT Perkebunan Nusantara IV Medan and to find out whether the payroll accounting information system implemented has good internal control.This research method uses a descriptive research approach and types of qualitative and quantitative data.Data collection techniques in this study using interviews and documentation techniques. The data analysis technique used in this research is descriptive analysis. The results of this study are the payroll accounting information system at PT Perkebunan Nusantara IV Medan has been running effectively. From the research results it can be explained that the employee payroll system at PT Perkebunan Nusantara IV Medan is carried out by bank transfer to the account of each employee which is calculated using the payroll application based on basic salary, allowances and deductions. Internal Control at PT Perkebunan Nusantara IV Medan has been running quite effectively, because every payroll transaction that is carried out has been verified and re-examined for accuracy before salary payment is made. Keywords: Accounting Information System, Payroll, Internal Control